2018
DOI: 10.1186/s13148-018-0563-3
|View full text |Cite
|
Sign up to set email alerts
|

The polyphenol quercetin induces cell death in leukemia by targeting epigenetic regulators of pro-apoptotic genes

Abstract: BackgroundIn the present study, we investigated the molecular mechanisms underlying the pro-apoptotic effects of quercetin (Qu) by evaluating the effect of Qu treatment on DNA methylation and posttranslational histone modifications of genes related to the apoptosis pathway. This study was performed in vivo in two human xenograft acute myeloid leukemia (AML) models and in vitro using HL60 and U937 cell lines.ResultsQu treatment almost eliminates DNMT1 and DNMT3a expression, and this regulation was in part STAT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 44 publications
2
41
0
1
Order By: Relevance
“…Quercetin contributes signifi cantly to brain development (1,2). The most important feature of the quercetin compound is its high antioxidant activity in cells (3). Quercetin compound was reported as anti-infl ammatory, antiviral, antioxidant, anti-carcinogenic and psychostimulant agent (4).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin contributes signifi cantly to brain development (1,2). The most important feature of the quercetin compound is its high antioxidant activity in cells (3). Quercetin compound was reported as anti-infl ammatory, antiviral, antioxidant, anti-carcinogenic and psychostimulant agent (4).…”
Section: Introductionmentioning
confidence: 99%
“…It increased the apoptosis of leukemic cell lines by inducing demethylation and the transcriptional activation of pro-apoptotic proteins. [86] In vitro: KG-1 cells Improved the efficacy of TRAIL in apoptosis induction by upregulating the expression of DR4 and DR5 and downregulating several antiapoptotic proteins like XIAP, c-IAP1 and c-IAP2. [87] AML, acute myeloid leukemia; APL, acute promyelocytic leukemia; ATRA, all-trans retinoic acid; ERβ, estrogen receptor beta; TNFα, tumor necrosis factor alpha; mTOR, mammalian target of rapamycin; FLT3, fms like tyrosine kinase 3; ANXA1, Annexin A1; 2-DG, 2-deoxy-D-glucose; ERK, extracellular signal-regulated kinase; DNMT, DNA methyltransferase; HDAC, histone deacetylase; ROS, reactive oxygen species; TRAIL, TNF-related apoptosis-inducing ligand; DR, death receptor; XIAP, X-linked inhibitor of apoptosis protein; c-IAP, cellular inhibitor of apoptosis.…”
Section: Agent Model(s) Summary Of Results and Underlying Mechanisms mentioning
confidence: 99%
“…This effect was partly mediated by ERK activation, as co-incubation with an ERK inhibitor partially abrogated quercetin-induced apoptosis [85]. A recent study also showed that the enhancement of apoptosis by quercetin may partly be caused by the inactivation of DNA methylases resulting from the proteasomal degradation of class I histone deacetylases (HDACs), which leads to increased histone acetylation in the promotor regions of pro-apoptotic genes [86]. In particular, this led to the increased transcription of DAPK1, BCL2L11, BAX, APAF1, BNIP3 and BNIP3L, which promoted AML cell apoptosis [86].…”
Section: Quercetinmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Moreover, it has been suggested that Q could induce apoptosis via re-expression and inhibition of DNA methylation of apoptotic genes in cancer cell lines. 30 However, many studies indicated that the application of Q has been limited by its low solubility, low bioavailability, and also it showed poor percutaneous and circulation absorption. 7,31,32 Therefore, to solve this problem, many researchers have attempted to improve the bioavailability forms of Q via chemical modifications, including Q-loaded liposomes and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%